Adrenal Steroids Modulate Fibroblast-Like Synoviocytes Response During B. abortus Infection - Gentilini, María Virginia; Giambartolomei, Guillermo Hernán; Delpino, María Victoria (Frontiers in Endocrinology, 2019)
Brucella abortus stimulates an inflammatory immune response that stimulates the endocrine system inducing the secretion of dehydroepiandrosterone (DHEA) and cortisol. In humans, the active disease is generally present as osteoarticular brucellosis. In previous studies we showed that B. abortus infection of synoviocytes creates a proinflammatory microenvironment. We proposed to determine the role of cortisol and DHEA on synoviocytes and infiltrating monocytes during B. abortus infection. Cortisol inhibited IL-6, IL-8, MCP-1, and MMP-2 secretion induced by B. abortus infection in synovial fibroblast. Cortisol-mediated MMP-2 inhibition during B. abortus infection was reversed by IL-6. DHEA inhibited B. abortus-induced RANKL up-regulation in synovial fibroblast through estrogen receptor (ER). B. abortus infection did not modulate glucocorticoid receptor (GR) expression. Cell responses to cortisol also depended on its intracellular bioavailability, according to the activity of the isoenzymes 11β-hydroxysteroid dehydrogenase (HSD) type-1, 11β-HSD2 (which are involved in cortisone-cortisol interconversion). B. abortus infection did not modify 11β-HSD1 expression and GRα/β ratio in the presence or not of adrenal steroids. Supernatants from B. abortus-infected monocytes induced 11β-HSD1 in synovial cells. Administration of cortisone was capable of inhibiting the secretion of RANKL by synoviocytes mimicking cortisol´s effect. These results go along with previous observations that highlighted the ability of synovial tissue to secrete active steroids making it an intracrine tissue. This is the first study that contributes to the knowledge of the consequence of adrenal steroids on synoviocytes in the context of a bacterial infection.